Dual-function antimicrobial-antibiofilm peptide hybrid to tackle biofilm-forming Staphylococcus epidermidis - Mathira Wongchai; Saharut Wongkaewkhiaw; Sakawrat Kanthawong; Sittiruk Roytrakul; Ratchaneewan Aunpad (BMC, 2024)
Abstract Background Due to their resistance and difficulty in treatment, biofilm-associated infections are problematic among hospitalized patients globally and account for 60% of all bacterial infections in humans. Antibiofilm peptides have recently emerged as an alternative treatment since they can be effectively designed and exert a different mode of biofilm inhibition and eradication. Methods A novel antibiofilm peptide, BiF, was designed from the conserved sequence of 18 α-helical antibiofilm peptides by template-assisted technique and its activity was improved by hybridization with a lipid binding motif (KILRR). Novel antibiofilm peptide derivatives were modified by substituting hydrophobic amino acids at positions 5 or 7, and both, with positively charged lysines (L5K, L7K). These peptide derivatives were tested for antibiofilm and antimicrobial activities against biofilm-forming Staphylococcus epidermidis and multiple other microbes using crystal violet and broth microdilution assays, respectively. To assess their impact on mammalian cells, the toxicity of peptides was determined through hemolysis and cytotoxicity assays. The stability of candidate peptide, BiF2_5K7K, was assessed in human serum and its secondary structure in bacterial membrane-like environments was analyzed using circular dichroism. The action of BiF2_5K7K on planktonic S. epidermidis and its effect on biofilm cell viability were assessed via viable counting assays. Its biofilm inhibition mechanism was investigated through confocal laser scanning microscopy and transcription analysis. Additionally, its ability to eradicate mature biofilms was examined using colony counting. Finally, a preliminary evaluation involved coating a catheter with BiF2_5K7K to assess its preventive efficacy against S. epidermidis biofilm formation on the catheter and its surrounding area. Results BiF2_5K7K, the modified antibiofilm peptide, exhibited dose-dependent antibiofilm activity against S. epidermidis. It inhibited biofilm formation at subinhibitory concentrations by altering S. epidermidis extracellular polysaccharide production and quorum-sensing gene expression. Additionally, it exhibited broad-spectrum antimicrobial activity and no significant hemolysis or toxicity against mammalian cell lines was observed. Its activity is retained when exposed to human serum. In bacterial membrane-like environments, this peptide formed an α-helix amphipathic structure. Within 4 h, a reduction in the number of S. epidermidis colonies was observed, demonstrating the fast action of this peptide. As a preliminary test, a BiF2_5K7K-coated catheter was able to prevent the development of S. epidermidis biofilm both on the catheter surface and in its surrounding area. Conclusions Due to the safety and effectiveness of BiF2_5K7K, we suggest that this peptide be further developed to combat biofilm infections, particularly those of biofilm-forming S. epidermidis.